VOT merger in Heritage Korean in Toronto. (17th June 2016) - Kang, Yoonjung; Nagy, Naomi
Abstract: Korean has a typologically unusual three-way laryngeal contrast in voiceless stops among aspirated, lenis, and fortis stops. Seoul Korean is undergoing a female-led sound change in which aspirated stops and lenis stops are merging in voice onset time (VOT) and are better distinguished by the F0 (fundamental frequency) of the following vowel than by their VOT, in younger speakers' speech. This paper compares the VOT pattern of Homeland (Seoul) and Heritage (Toronto) Korean speakers and finds that the same change is in progress in both. However, in the heritage variety, younger speakers do not advance the change, unlike their Seoul counterparts. Rather they have leveled off or are perhaps reversing the change, and there is very little sex difference among the younger heritage speakers' patterns. We consider possible accounts of the differences between the Seoul and Toronto patterns, building our understanding of how language-internal variation operates in bilingual speakers, a topic that has received relatively less attention in the variationist literature.